(untitled) (Research, Society and Development, 2022)
To analyze the sociodemographic and academic background factors associated with the knowledge and attitudes of nursing students about sexual behavior and Sexually Transmitted Infections in the elderly. Cross-sectional study, carried out with 88 nursing students enrolled from the fifth to the tenth semester of a public university. Data collection took place in 2020, using a self-administered online questionnaire on sociodemographic characteristics, academic background, knowledge and attitudes about sexual behavior and STIs in older people. In the descriptive analysis, absolute and relative frequencies were calculated for the categorical variables. For knowledge and attitude, mean, median, interquartile distance and standard deviation were calculated according to sociodemographic and academic background variables. Linear and multiple regression were performed to assess variables associated with knowledge and attitudes, adopting a significance level of 5%. The variables associated with the students’ knowledge were: age group from 27 to 39 years (beta=1.45; 95%CI:0.18-2.07); contact with the elderly (beta=1.06; 95%CI:0.48-2.07); STI complementary activity on elderly people (beta=2.43; 95%CI:1.01-3.84); seventh (beta=2.22; 95%CI:1.08-3.37) and ninth (beta=1.67;95%CI:0.52-2.82) ongoing semesters. As for attitudes, participating in complementary activities remained associated in the multiple model (beta=10.24; 95%CI:1.17-19.31). Nursing students aged 27 years or older, who have close contact with the elderly, who attend between the seventh and tenth semesters and who have already participated in complementary activities have a higher level of knowledge about sexual behavior and STIs in elderly people. Those who participated in complementary activities have more positive attitudes